2019
DOI: 10.1021/acs.jpcc.9b01166
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Water on Pristine, S- and N-Doped TiO2(001) Nanotube Surfaces: A DFT + U Study

Abstract: Using density functional theory calculations, we study the structure, energetics, and the photoelectrochemical oxidation of water on pristine, S-, N-, and (N + S)-doped anatase TiO2(001) nanotube (NT) surfaces. We found that water adsorbs molecularly on pristine and S-doped surfaces, while N doping promotes dissociative adsorption (both in the presence and absence of the S codopant) and leads to more favorable adsorbate–substrate interactions. Under photoelectrochemical conditions, OH groups are the most stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…13,14 Density functional theory (DFT)+U study revealed that N-doping promotes dissociative water adsorption, leading to favorable adsorbate-substrate interactions and stabilization of OH groups at the TiO 2 surface. 15 Therefore, combined metal modification and non-metal doping is a good approach for catalyst tailoring. [16][17][18] This, however, should be treated carefully, since dopants introduced in the TiO 2 lattice can have states near the conduction band (CB), allowing the formation of mid-gaps that can accelerate electron-hole recombination rates and hinder photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Density functional theory (DFT)+U study revealed that N-doping promotes dissociative water adsorption, leading to favorable adsorbate-substrate interactions and stabilization of OH groups at the TiO 2 surface. 15 Therefore, combined metal modification and non-metal doping is a good approach for catalyst tailoring. [16][17][18] This, however, should be treated carefully, since dopants introduced in the TiO 2 lattice can have states near the conduction band (CB), allowing the formation of mid-gaps that can accelerate electron-hole recombination rates and hinder photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 193 ] While solo N dopant hardly optimize the photoinduced water oxidation kinetics compared with S dopant, but the S and N codoping method can improve the PEC performance of TiO 2 effectively by means of lowering the required energy. [ 188,194 ] s discussed in Sections 2 to 5, the multihierarchical composited TiO 2 photoelectrodes show better PEC performance as well as optical response to visible lights due to the interior heterojunction interfaces induced built‐in electric field, as well as the exterior designed nanoarchitectures and photoabsorbers (or cocatalysts).…”
Section: Charge Transfer In Ions Doped 1d Tio2 Constructed Photoelectmentioning
confidence: 99%
“…N, S, B, F, and P dopants can shift the VB of TiO 2 toward water oxidation potential, while these shallow acceptor doping would trigger electron mobility recession owing to the electronic attraction of acceptor dopants. [188][189][190][191][192] According to the research of Asahi et al, N is the most suitable dopant to form new energy state well overlapped with O 2p orbital leading to proceed visible lights induced water oxidation with stable microstructure. [183] With the introduced oxygen defects and Ti 3+ color centers in N doped TiO 2 , N doped TiO 2 show good progress on visible lights harvest and electronic conductivity.…”
Section: Charge Transfer In Ions Doped 1d Tio 2 Constructed Photoelecmentioning
confidence: 99%
“…This included a study of water adsorption on 2D-representation of 9-layered TiO 2 nanotube, on clean and doped surfaces [ 9 ]. The CFVS model was also used to study the structure, energetics, and the photoelectrochemical oxidation of water on the aforementioned structures by means of the DFT + U method and a plane-wave-based computational code Quantum Espresso [ 10 , 11 ]. The results of these studies are summarized in a review [ 12 ].…”
Section: Introductionmentioning
confidence: 99%